DAMPAK PEMBERIAN MIKROPLASTIK POLIETHILEN PERORAL TERHADAP HITUNG JENIS SEL LEUKOSIT DARAH RATTUS NORVEGICUS STRAIN WISTAR - Yudhiakuari Sincihu (UNUSA Press, 2022)
Microplastics have been identified as food chain contaminants. Most plastic polymers are polyethylene. Microplastics in the gastrointestinal tract will undergo persorption through the cell gap at the end of the intestinal villi into the blood circulation to be distributed throughout the tissue. It is suspected that microplastics will trigger chronic inflammation. The aim of the study was to analyze the impact of oral exposure to polyethylene microplastics on the blood leukocyte cell count. Pure experimental research with posttest only control group design. Random allocation was used to divide 30 Rattus norvegicus wistar strains into each group of the same number. There were 4 exposure groups with a dose of D1=0.0375mg, D2=0.075mg, D3=0.15mg, D4=0.6mg of microplastic particles per day through an oral probe and 1 control group that was not given microplastics. Exposure is given for 90 days. One-way ANOVA test was used to analyze the difference in values ​​between groups. The results of this study show an increasing trend in the mean of leukocyte biomarkers, neutrophil and basophil counts in the exposure group (1,2,3,4) compared to the control (0). Statistical tests showed significant values ​​for leukocyte biomarkers (P= .048) and basophils (P= .040), where more exposure doses will cause an increase in the level of these biomarkers in the blood. Oral exposure to polyethylene microplastics had an effect on leukocytosis in the blood of Rattus norvegicus wistar strain.